Endosomal entry regulates Notch receptor activation in Drosophila melanogaster. - Vaccari, T.; Lu, H.; Kanwar, R.; Fortini, M.E.; Bilder, D. (Journal of Cell Biology, 2008)
Signaling through the transmembrane receptor Notch is widely used throughout animal development and is a major regulator of cell proliferation and differentiation. During canonical Notch signaling, internalization and recycling of Notch ligands controls signaling activity, but the involvement of endocytosis in activation of Notch itself is not well understood. To address this question, we systematically assessed Notch localization, processing, and signaling in a comprehensive set of Drosophila melanogaster mutants that block access of cargo to different endocytic compartments. We find that gamma-secretase cleavage and signaling of endogenous Notch is reduced in mutants that impair entry into the early endosome but is enhanced in mutants that increase endosomal retention. In mutants that block endosomal entry, we also uncover an alternative, low-efficiency Notch trafficking route that can contribute to signaling. Our data show that endosomal access of the Notch receptor is critical to achieve physiological levels of signaling and further suggest that altered residence in distinct endocytic compartments could underlie pathologies involving aberrant Notch pathway activation.